Antigen Presentation and T Cell Response in Umbilical Cord Blood and Adult Peripheral Blood - Grozdics, Eniko; Toldi, Gergely (Journal of Hematology Research, 2014)
The efficiency of the immune response is well-known to be decreased in the perinatal period compared to adulthood. Several factors may play a role in this finding, including immaturity of adaptive immune responses, as well as alterations in the prevalence and functionality in elements of humoral and cellular immune reactions compared to adult-type immunity. The process of antigen presentation and adequate T cell function are cornerstone features in coordinating the immune response already at this early age. Over the recent decades, several studies have revealed remarkable details that contribute to these alterations. However, many aspects of the exact mechanisms are still not fully understood. In this review, we aim to summarize current knowledge of studies of altered cell prevalence and functionality that contribute to differences of antigen presentation and the T cell immune response between the perinatal and adult periods. Decreased level of antigen presentation, lower expression of costimulatory molecules, lower Th1 and Th17 response, and deficient function of regulatory elements are the most important differences in CB compared with adult peripheral blood. These differences are of practical importance from two distinct aspects. First, the decreased efficiency of the immune response plays an important role in the development of several diseases affecting preterm and term neonates, as well as in a higher incidence of infections compared to adults. Second, umbilical cord blood (UCB)-derived hematopoietic stem cells are widely used in the treatment of different hematological and immunological disorders. The prevalence of graft-versus-host disease (GVHD) is lower upon UCB-derived stem cell transplantation compared to adult peripheral blood or bone marrow-derived stem cells. Therefore, the deeper understanding of the mechanisms contributing to a decreased T cell response is of importance in improving therapeutic efficiency in related disorders.